ANALISIS KEBERAGAMAN USAHA RUMAH TANGGA PERTANIAN LAHAN KERING DI KABUPATEN BANYUMAS - Kusmantoro Edy Sularso; Tatang Widjojoko (University of Jember, 2009)
In Banyumas Regency, parts of dry land owned by farmers are used for cultivating dry land rice, food crops, cassava, and cattle farm. Aims of the research were 1) to analyze variations of farmers’ house hold efforts, 2) to calculate amount of farmers’ house hold income of on farm, off farm, and non farm sectors, 3) to know the contribution of various income from off farm and non farm sectors to farmers’ house hold income, 4) to know factors affecting variation levels of farmers house hold efforts. The method of the research used was a survey using 75 respondents. Efforts conducted by the house hold members were varied, consisting of 1) animal husbandry efforts such as duck, chicken, and goat cattle; 2) attempts on services of building labour, carpenter, and mason; 3) business on major needs, carpenter workshop, coconut sugar craftsman; 4) village officers, and 5) civil servants. Income of the dry land rice farm provided the highest contribution to the house income of the on farm. Meanwhile the income of animal husbandry efforts gave the highest contribution to the house income of the off farm. The income obtained from by the farmers’ house hold from the business gave the highest contribution to the income of the farmers’ house hold of the non farm business. The non farm income had the highest contribution to the house hold income of the farmers.Key words: house hold income, effort variation, farmers’ income.